2013
DOI: 10.1021/am401222p
|View full text |Cite
|
Sign up to set email alerts
|

PDMS/Kapton Interface Plasma Treatment Effects on the Polymeric Package for a Wearable Thermoelectric Generator

Abstract: The present work highlights the progress in the field of polymeric package reliability engineering for a flexible thermoelectric generator realized by thin-film technology on a Kapton substrate. The effects of different plasma treatments on the mechanical performance at the interface of a poly(dimethylsiloxane) (PDMS)/Kapton assembly were investigated. To increase the package mechanical stability of the realized wearable power source, the Kapton surface wettability after plasma exposure was investigated by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The scalable solution for a wearable thermal harvester has become a research frontier for wearable TEGs. Some pioneering works utilize a wave-like shaped polymer substrate 8 to hold thin film-based TE materials upright in a practical direction for the heat flow. Others use island-like inorganic or metal TE materials pressed into a soft fabric with an adhesive 9 , electrochemical deposition 10 , or screen printing technique 11 to satisfy the demand of flexibility considering the thermal gradient.…”
mentioning
confidence: 99%
“…The scalable solution for a wearable thermal harvester has become a research frontier for wearable TEGs. Some pioneering works utilize a wave-like shaped polymer substrate 8 to hold thin film-based TE materials upright in a practical direction for the heat flow. Others use island-like inorganic or metal TE materials pressed into a soft fabric with an adhesive 9 , electrochemical deposition 10 , or screen printing technique 11 to satisfy the demand of flexibility considering the thermal gradient.…”
mentioning
confidence: 99%
“…Due to its excellent biocompatibility and biologically relevant mechanical properties, it has the potential to be a fiber coating material. In the fabrication of integrated optical circuits and circuits [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], PDMS is usually made into a special waveguide in an integrated system [ 14 , 15 ]. After a large number of experimental studies, it was found that the integrated system prepared by PDMS has the characteristics of low loss, high temperature stability, and sufficient mechanical stability, and the sensitive characteristic of temperature and humidity also began to be concerned.…”
Section: Sensors Coated With the Pdmsmentioning
confidence: 99%
“…The images were acquired with a CMOS camera and drop-analysis was conducted aerwards. 60,61 The measurements were conducted in the laboratory with a controlled temperature of 23 C and with 50% average relative humidity. The microstratch tests were performed using a Micro-scratch test instrument (CSM, Switzerland) equipped with a diamond tip of 200 microns in diameter.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%